2016
DOI: 10.1021/acs.nanolett.6b00460
|View full text |Cite
|
Sign up to set email alerts
|

Strings-to-Rings Transition and Antiparallel Dipole Alignment in Two-Dimensional Methanols

Abstract: Structural order emerging in the liquid state necessitates a critical degree of anisotropy of the molecules. For example, liquid crystals and Langmuir monolayers require rodor disc-shaped and long-chain amphiphilic molecules, respectively, to break the isotropic symmetry of liquids. In this Letter we present results from molecular dynamics simulations demonstrating that in two-dimensional liquids, a significantly smaller degree of anisotropy is sufficient to allow structural organization. In fact, the condense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…Comparison of the snapshots shows that our systems and confined methanol display very similar trends in structure depending changes with the temperature. This is further confirmed by similarities in the radial distributions functions as well as temperature dependence of the energy and hydrogen bonding 77 .…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Comparison of the snapshots shows that our systems and confined methanol display very similar trends in structure depending changes with the temperature. This is further confirmed by similarities in the radial distributions functions as well as temperature dependence of the energy and hydrogen bonding 77 .…”
Section: Discussionsupporting
confidence: 62%
“…Morishige and Kawano 76 argue that in a very small nanotube methanol shows possible vitrification observed in the diffraction pattern throughout a range of temperatures. In a recent article on methanol confined between two graphene sheets, authors Zangi and Roccatano 77 show the formation of long chain phases at the lower temperature and the transition to small chains and rings at the high temperature for a dense methanol system. Comparison of the snapshots shows that our systems and confined methanol display very similar trends in structure depending changes with the temperature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we investigated the structure and self-assembly of methanol molecules confined between two, or adsorbed on, graphene sheets. 12 In the process of extending this study for larger molecules, we tested the behavior of the bulk liquid phase (in three dimensions) at ambient conditions of a series of larger alcohols. However in this case, we observed that within few hundred nanoseconds, 1-octanol, 1-nonanol, and 1-decanol, when described by the OPLSAA force-field, spontaneously undergo a sharp first-order transition from liquid to solid.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Yet, biological self-assembly usually occurs at fast rates and with high precision, making it particularly interesting although still poorly understood. 14,15 To date, the self-assembly of small molecules has primarily been studied in extreme cases where systems are under confinement 16 or at low temperatures 17 so as to force the molecules to remain long enough near the solid's surface for supramolecular structures to form. Examples in ambient conditions are scarce, with limited insights into the process.…”
Section: Introductionmentioning
confidence: 99%